Development of Basra Port(1956-1968) - Aiazaz Dakhel, Lect. Dr. Saad (Basra studies journal, 2024)
Ports are among the most important places in the world where trade and the economy thrive, especially in countries with ports that overlook global seas. The city of Basra is one of the most significant cities with important maritime ports. These ports have contributed to the flourishing of the Iraqi economy and the movement of trade and maritime transport. The Port of Basra is one of the most important ports in Iraq and the Arabian Gulf, having witnessed development since its establishment by the British occupation of Iraq in 1914.